Typhoon and Flooding Disasters’ Lived Experiences of Loboc Residents in Bohol, Philippines - Melinda Calipusan-Elnar; Ferdinand Tesado Abocejo (CV. Literasi Indonesia, 2021)
This study described the meaning of lived experiences of the municipal leaders of Loboc, Bohol, Philippines, prior, during, and after typhoon “Seniang” in 2014. It investigated the initiatives and practices of the local government unit (LGU) and captured the household experiences through a qualitative research approach following the Husserlian descriptive phenomenology utilizing Colaizzi’s method of data analysis. Purposive sampling was employed through face-to-face interviews with 12 key informants after reaching saturation point. All narrative accounts were transcribed and served as the primary source of qualitative data. The extracted accounts were organized through thematic categorization yielding 77 significant statements, 28 formulated meanings, 15 clusters, and 4 emergent themes. These emergent themes include awareness of disaster, experiences during the disaster, good local governance practices, and experienced challenges. Grounded on these findings, it is concluded that effective disaster response and quick and successful recovery fundamentally depend on authentic and effective governance by Loboc local leaders concretized through collaborative, concrete observance, implementation of responsive policy processes and the harmonious team works among community members. Altogether, proactive involvement makes a community more resilient. The researchers recommend that Loboc local leaders, employees, and residents, altogether put a premium on active participation, profess a positive outlook with enduring commitment to immediately rebound from any experienced disaster.